1997
DOI: 10.1063/1.118791
|View full text |Cite
|
Sign up to set email alerts
|

Elastic constants and crystal anisotropy of titanium diboride

Abstract: In this study, the elastic constants of a titanium diboride (TiB2) single crystal were measured using resonant ultrasound spectroscopy. In contrast to previous work, the current results are consistent with the measured elastic constants of TiB2 polycrystals. In addition, the crystal anisotropy of TiB2 was examined. The current data show that the elastic properties of TiB2 are much more isotropic than previously considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
47
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(62 citation statements)
references
References 10 publications
13
47
2
Order By: Relevance
“…The values of elastic constants for TiB 2 determined in the present study agree well with those previously reported by Spoor et al [20] but not completely with those reported by Gilman et al [21]. In particular, the values of c 12 and c 13 determined in the present study are considerably smaller than those reported by Gilman et al [21].…”
Section: Monocrystal Elastic Constantssupporting
confidence: 84%
See 1 more Smart Citation
“…The values of elastic constants for TiB 2 determined in the present study agree well with those previously reported by Spoor et al [20] but not completely with those reported by Gilman et al [21]. In particular, the values of c 12 and c 13 determined in the present study are considerably smaller than those reported by Gilman et al [21].…”
Section: Monocrystal Elastic Constantssupporting
confidence: 84%
“…This is because of the exceptionally small values of c 44 Table 3 Monocrystal elastic constants at 300 K in the form of c ij = c ij(300K) + k (T À 300) where c ij(300K) , k and T stand for the elastic constant at 300 K, numerical constant and temperature in Kelvin, respectively, and anisotropic parameters (c 33 /c 11 and c 44 /c 66 ) at 300 K. The numerical constants are shown in the parentheses. Previously reported monocrystal elastic constants for TiB 2 are also tabulated for comparison [20,21]. Table 4 Values of Young's moduli and reciprocals of linear compressibilities along the a-and c-axes at 300 K.…”
Section: Polycrystalline Elastic Modulimentioning
confidence: 99%
“…(2)(3)(4)(5)(6)(7)(8). The value of Θ D = 755 K for α-Li 3 N at P = 0 may be compared to 1016K for MgB 2 [33] and 743K for TiB 2 [34]. It is thus found that the value is closer to that of TiB 2 than to MgB 2 .Further Θ D increases as pressure increases.…”
Section: Debye Temperature and Elastic Properties Of Polycrystallinmentioning
confidence: 67%
“…It is suggested that in part the strength is due to the so-called "nanocomposite" microstructure comprised of AlMgB 14 and TiB 2 , although the hardness of each individual phase is believed to be less than the hardness of the composite. [6] There have been many studies examining TiB 2 , [7][8][9][10] but the orthorhombic boride family has received much less attention and is therefore the focus of this letter.…”
mentioning
confidence: 99%